(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The stratigraphic revislon of the Iower Cretaceous successions from the Gargano peninsula provides new lithostratigraphic data ; two formations could be distinguished: the Vico del Gargano Limestones and the Mattinata Limestones corresponding to basin and talus deposits respectively. New micropaleontological data are given concerning the definition and the boundaries of Berriasian p.p. Valanginian p.p. The Aptian is well characterized and the substages Bedoulian, Gargasian and ClansayeSian are clearly separated by mean of significant foraminiferal assemblages, especially in the talus sedimentary successions. Hauterivian—Barremian p.p. and Albian intervals are poorly defined. From a sedimentological point of view basin and talus successions are clearly differentiated. These data will be used for further paleogeographic reconstructions.